A study on the genetic polymorphisms of CYP3A5 among the Orang Asli in Malaysia using a next generation sequencing platform - Geik Yong Ang; Choo Yee Yu; Richard Johari James; Aminuddin Ahmad; Thuhairah Abdul Rahman; Fadzilah Mohd Nor; Syahrul Azlin Shaari; Adzrool Idzwan Ismail; Lay Kek Teh; Mohd Zaki Salleh (Taylor & Francis Group, 2018)
Background: CYP3A5 is the predominant sub-family of biotransformation enzymes in the liver and the genetic variations in CYP3A5 are an important determinant of inter-individual and inter-ethnic differences in CYP3A-mediated drug disposition and response. Aim: This study aims to investigate the genetic polymorphisms of CYP3A5 among the Orang Asli in Peninsular Malaysia using a next generation sequencing platform. Methods: Genomic DNAs were extracted from blood samples of the three main Orang Asli tribes and whole-genome sequencing was performed. Results: A total of 61 single nucleotide polymorphisms were identified and all the SNPs were located in introns except rs15524, which is in the 3'UTR, and 11 of these polymorphisms were novel. Two allelic variants and three genotypes were identified in the Orang Asli. The major allelic variant was the non-functional CYP3A5*3 (66.4%). The percentages of Orang Asli with CYP3A5*3/*3 (47.2%) and CYP3A5*1/*3 (38.1%) genotypes are more than twice the percentage of Orang Asli with CYP3A5*1/*1 (14.8%) genotype. Almost half of the Orang Asli harboured CYP3A5 non-expressor genotype (CYP3A5*3/*3). Conclusions: The predominance of the CYP3A5 non-expressor genotype among the Orang Asli was unravelled and the findings in this study may serve as a guide for the optimisation of pharmacotherapy for the Orang Asli community.